Анализа на капацитетот за производство на електрична енергија кај повеќеакумулациски водостопански систем - Пановска Ф., Митовски С., Петковски Љ (Macedonian Committee on Large Dams - Skopje, 2019)
According to the Water Master Plan of 1973, in the lower basin of Crna Reka in Mariovo and Tikvesh regions, construction of three large hydro systems is planned: Chebren, Galishte and Tikvesh – as furthest down the river. From all three planned, only Tikvesh is build, back in 1969. The hydro system Tikvesh provides water primarily for irrigation of Tikvesh region, and right downstream from the dam the powerhouse is located where electricity is produced ever since 1969. Many studies and technical documentation that prove technical and economy feasibility of this system, has been prepared throughout the years. In this paper, with implementation of simulation mathematical models, prospective electricity production is estimated of a complex water resources system in the lower basin of Crna Reka, by implementing Chebren and Galishte as planned system, and Tikvesh – as the existing one.